Electrification of Compressor in Steam Cracker Plant: A Path to Reduced Emissions and Optimized Energy Integration - Joana Cordeiro Torcato; Rodrigo Silva; Mário Eusébio (ChemEngineering, 2025)
Electrification is a highly effective decarbonization and environmental incentive strategy for the chemical industry. Nevertheless, it may lead to downstream challenges in the process. This study analyzes the consequences of electrifying compressors within the steam cracker (SC) condensate system, focusing on the reduction in greenhouse gas (GHG) emissions and energy consumption without compromising the process’s energy efficiency. The aim is to study the impact that the reduction in steam expanded by turbines has on boiler feedwater (BFW) temperature and, subsequently, the behavior it triggers in fuel gas (FG) consumption and carbon dioxide (CO2) emissions in furnaces. It was concluded that condensate imports from the Energies and Utilities Plant (E&U) would increase by a factor of four, with approximately 60% of the imported condensate being cold condensate. The study revealed a mitigation of CO2 emissions, resulting in a 1.3% reduction and a reduction in FG consumption of 1.8% preventing an increase in site energy consumption by 795.4 kW in furnaces. Condenser optimization reduces CO2 emissions by 60%. Energy integration with quench water resulted in heat saving of 1824 kW in hot utility consumption and generating annual savings of EUR 2.3 M. The global carbon dioxide balance can achieve up to a 25% reduction.